2006
DOI: 10.1128/aem.72.3.2178-2184.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Single-Celled Ascaris suum Eggs by Low-Pressure UV Radiation

Abstract: 2 ), from 0-to 1.5-log inactivation can be expected, although at typical fluences (less than 1,000 J/m 2 ), the inactivation may be less than 1 log. When the eggs were decorticated (the outer egg shell layers were removed with sodium hypochlorite, leaving only the lipoprotein ascaroside layer) before exposure to UV, 1.80-؎ 0.32-log reduction (98.4%) was achieved with a fluence of 500 J/m 2 , suggesting that the outer eggshell layers protected A. suum eggs from inactivation by UV radiation. This protection may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 33 publications
3
39
0
5
Order By: Relevance
“…All of the heated samples were incubated in 50-ml plastic centrifuge tubes in a water bath. The quasi-collimated beam used for the UV experiments has been described previously (5). In brief, the suspensions of eggs were placed in 50-mm glass petri dishes and gently stirred under a quasi-collimated UV beam.…”
Section: Vol 72 2006 Qpcr Quantification Of Viable Ascaris Eggs 7865mentioning
confidence: 99%
“…All of the heated samples were incubated in 50-ml plastic centrifuge tubes in a water bath. The quasi-collimated beam used for the UV experiments has been described previously (5). In brief, the suspensions of eggs were placed in 50-mm glass petri dishes and gently stirred under a quasi-collimated UV beam.…”
Section: Vol 72 2006 Qpcr Quantification Of Viable Ascaris Eggs 7865mentioning
confidence: 99%
“…Due to its resistance to biocontrol mechanisms (6) Ascaris is a model organism for developing environmentally safe disinfection methods (7,22). The eggs can be rendered nonviable through natural processes using extreme heat (Ͼ40°C) or with UV radiation (4). The use of short-chain fatty acids (SCFA) is another possible method of controlling Ascaris.…”
mentioning
confidence: 99%
“…Maya et al [4] reported that four genera of helminth eggs, i.e., Ascaris lumbricoides, Ascaris suum, Toxocara canis and Trichuris trichiura, are sensitive to environmental conditions in the larval state in the sludge. Furthermore, a proper combination of pH, dryness and contact time with temperatures above 60 °C can be applied to inactivate the eggs, efficiently [4,23]. Unfortunately, external energy and chemical-dependent technologies are in general not feasible for developing countries because they are complex, not sustainable and expensive in terms of investment and operation and maintenance costs [4,17,18,24].…”
Section: Introductionmentioning
confidence: 99%